Influence of night length on home range size in the northern bat Eptesicus nilssonii - Frafjord, Karl (Mammalian Biology, 2013)
The northern bat Eptesicus nilssonii is widespread in Fennoscandia, with breeding populations well above the Arctic Circle. I studied this species at its extreme northern limit, at 69°N in Norway. I radio-tracked 17 bats from 2 maternity roosts during 2003–2006 to study the influence of the midnight sun and increasing lengths of darkness on activity (time spent out of roost) and home range size. Activity and home range was highly correlated with night length (light intensity); both increasing progressively with season. Bats were classified into 3 groups based on the time of the season they were tracked (basically July, August and September–October); short activity (average 1.57 h) and small home range (average 0.91 km2), medium activity (3.69 h) and medium-sized home range (4.58 km2), and long activity (4.80 h) and large home range (17.2 km2). Bats visited roosts several times during the night, and the duration of roost visits increased significantly by group. The number of periods out of roost increased from the first to the second group (1.45 vs. 2.36 flight periods per night), but insignificantly to the third group (2.37 flights). The most significant increase in activity and home range was associated with the first flight of juveniles in early August. These bats appeared to have a threshold level of around 1700 lux for activity out of roost, with little difference between light levels at emergence and return (the second group returned in significantly poorer light than they emerged in). Although the northern bat at this extreme latitude had adapted to the ambient light conditions, the bright nights under the midnight sun and the short season strongly reduced their window of opportunity for activity and may possibly reduce survival and reproductive success.